Implementation and Challenges of Carbon Tax to Reduce Emissions in Indonesia - Thalia Faz, Aisya; Ika Rahmawati; Oktavian Deo Widiarto; Rio Ferry Irfansyah (Jurnal Justice Dialectical, 2024)
Carbon tax is proposed as a policy to reduce greenhouse gas emissions in Indonesia, especially carbon dioxide (CO₂), which is the main cause of climate change. In the context of Indonesia, which accounts for about 2% of total global emissions, a carbon tax is expected to internalize the negative externalities of those emissions and drive the transition to clean energy. In this paper, we analyze the application of carbon tax as a strategy to reduce greenhouse gas emissions in Indonesia. We also identified and evaluated the challenges faced in implementing carbon tax policies, including resistance from industry and communities, as well as the complexity of setting fair and effective rates. Our results show that the implementation of a carbon tax has great potential in reducing greenhouse gas emissions and supporting sustainable development. However, the implementation of the carbon tax is also faced with various challenges that need to be overcome. Therefore, cooperation between government, industry, and society is needed to formulate effective and sustainable carbon tax policies. Through this analysis, it is hoped that solutions can be found to improve the effectiveness of carbon tax policies in reducing emissions and supporting environmental sustainability.